Preload monitoring of single nut ball screws based on sensor fusion. (May 2021) - Denkena, Berend; Bergmann, Benjamin; Schmidt, Alexander
Abstract: Unplanned machine downtimes lead to higher costs through reduced productivity. Machine availability is amongst others limited by the failure of wear-induced preload loss of ball screws. Therefore, attempts are made to monitor the preload. The high complexity and required robustness of preload monitoring leads to a low spreading in industry so far. This paper investigates the capability of sensor fusion based on principal component analysis to monitor preload loss of single nut ball screws. Features are investigated using different preload levels of the ball screw by selecting different ball-diameters. It is shown that this approach reliably detects the preload levels.